Raziskava možnosti uporabe ustrezno čiščene odpadne vode iz centralne čistilne naprave Koper in centralne čistilne naprave Piran - Drev, Darko (Gradbeni vestnik, 2023)
The Slovenian coast suffers from great lack of drinking water in the dry season. The Rižana water supply system does not have sufficient capacity and therefore buys water from Croatia and the Karst region. However, water consumption needs to be reduced during the summer months. The lack of water could be reduced if the wastewater at the Koper and Piran wastewater treatment plants was properly treated and then used. The use of water containing certain concentrations of nutrients does not affect some industrial production processes, and it would be beneficial to agriculture because fewer additional nutrients would need to be applied to agricultural land. This would not require any major financial resources, but only a proper reconstruction of the Koper and Piran wastewater treatment plants. In order to use the treated water properly for technological, agricultural or sanitary purposes, its transport to potential users would have to be ensured.
Keywords: čistilne naprave; membrane wastewater treatment plants; membranske čistilne naprave; odpadna voda; ponovna raba vode; wastewater; wastewater treatment plants; water reuse